Evaluating the Role of Professional Identity and Future Orientation in Enhancing Learning Engagement Among Special Education Majored Students: A Moderated Mediation Effect - Tan Shaojie (SAGE Open)
This research delves into the intricate relationship between special education majored students’ perceptions of classroom atmosphere and their learning engagement, while also investigating the mediating influence of professional identity and the moderating effect of future orientation. A survey involving 582 special education majored students was conducted, utilizing the Student Perceived Class Atmosphere Scale, Learning Engagement Scale, College Students Professional Identity Scale, and Future Orientation Questionnaire for data collection. The collected data underwent thorough organization and statistical analysis using SPSS 24 software. The research results show that: (1) Special education majored students’ perception of class atmosphere has a positive predictive effect on learning engagement; (2) Professional identity plays an important mediating role between perception of class atmosphere and learning engagement; (3) Future orientation significantly moderates the direct path between special education majored students’ perceived class atmosphere and learning engagement, and moderated the second half of mediation models, the relationship between professional identity and special education majored students’ learning engagement. These research results enrich the theory of special education and have practical significance for improving the quality of special education teacher training.